(untitled) (The Pakistan Development Review, 2016)
Economic growth depends on many factors like the traditional factors of capital, labour and technological advancement and the somewhat novel factors of financial development and the nature of political regime. The relationship between the nature of political structure and economic growth is quite complicated. There may be direct and indirect impacts of the nature of political set up on economic growth. However, these channels remain un-explored to larger extent. The present study is conducted to analyse economic growth under democracy and dictatorship for a considerably larger set of countries from 1974 to 2013. The indirect impact of democracy on economic growth is analysed through an unexplored channel of financial sector performance, which is expected to be sensitive to regime type. The direct impact of democracy is found to be positively significant on economic growth. Likewise, direct impact of financial sector performance on economic growth is also found to be positive and significant. However, democracy had negative indirect impact on economic growth through financial sector but the magnitude of this indirect negative impact is minute enough to be ignored as compared to large individual direct effects of democracy and financial sector. JEL Classification: O40, O43, O16 Keywords: Economic Growth, Democracy, Dictatorship, Financial Sector Performance